An analysis of the urban heat island of Venice mainland. (December 2015) - Peron, F.; De Maria, M.M.; Spinazzè, F.; Mazzali, U.
Abstract: In Italy, as in the rest of Europe, serious land degradation processes are occurring, mostly due to rural abandonment, urbanization and infrastructure development. In particular Veneto, the region around Venice, has undergone considerable land use and land cover change in the last decades. This work integrates field observations and numerical simulations to study the urban heat island (UHI) effect in the mainland part of Venice. The numerical study was performed using ENVI-met, an environment and micro-climatic simulation tool. Different mitigation scenarios are evaluated in a case study area. The study aims to explore the factors that contribute to urban heat island development proposing practical, feasible and specific solutions for mitigating their effects. The focus of the analysis is, in particular, on the use of permeable surfaces vegetative soil or grassed parking instead of conventional asphalt or cement pavement as soil compensation mechanisms for soil loss. The replacement of traditional roofs with cool or green ones is also considered.